01 FAKTOR - FAKTOR YANG MEMPENGARUHI PERMINTAAN DODOL BERAS KETAN DI KABUPATEN MAROS (Studi Kasus di Pammelakkang Je’ne Kelurahan Allepolea Kecamatan Lau Kabupaten Maros) - Jurnal Agribis; Herlina Herlina; Mohammad Anwar Sadat; Arifin Arifin (Jurnal Agribis, 2017)
The purpose of this study is to determine the factors that influence consumer demand for sticky rice dodol and find out how consumers' perceptions of sticky rice dodol and study every problem that occurs in dodol business management. So that we can knowledge and solve every problem that exists, especially consumer demand. Because this study has an unlimited population, the sampling technique is using accidental sampling, which is a sampling technique that is based on chance meeting with researchers and can be used as a sample if it is seen that people who happen to be met are suitable as data sources. Data obtained from questionnaires which are then processed and analyzed using multiple regression analysis techniques. This analysis includes: validity and reliability test, classic assumption test, multiple regression analysis, hypothesis testing through t test and F test, and analysis of the coefficient of determination (R2).